Effect of Patients’ Endocrine Status on Effectiveness of Treatment with Rituximab: State of the Art - YuV Komoza; VA Komoza; SV Chernavskii; OA Rukavitsyn (Клиническая онкогематология)
The non-Hodgkin’s lymphoma morbidity rate is gradually increasing, and its peak is registered in patients aged 45–60 years. At the same time, the world population steadily becomes older. Monoclonal antibodies (Rituximab) have been used in the treatment of patients with CD20-positive lymphomas for more than 20 years. The use of this drug enhanced the effectiveness of the therapy significantly. However, when patients were divided into groups by age and sex, better results were obtained in the group of women over 60 years. The review presents the results of several studies which have analyzed the effectiveness of rituximab-based schemes in patients depending on their sex and age, using different dosages and administration regimens. The article also presents our personal conclusions about the possible causes of the differences in efficacy of the drug in some patient populations. Identification of the causes contributing to the improvement of the effectiveness of rituximab in elderly women may significantly change approaches to the treatment of lymphomas in patients of both sexes.